Accurate and fast implementation of soybean pod counting and localization from high-resolution image - Yu, Zhenghong; Wang, Yangxu; Ye, Jianxiong; Liufu, Shengjie; Lu, Dunlu; Zhu, Xiuli; Yang, Zhongming; Tan, Qingji (Frontiers in Plant Science, 2024)
Soybean pod count is one of the crucial indicators of soybean yield. Nevertheless, due to the challenges associated with counting pods, such as crowded and uneven pod distribution, existing pod counting models prioritize accuracy over efficiency, which does not meet the requirements for lightweight and real-time tasks. To address this goal, we have designed a deep convolutional network called PodNet. It employs a lightweight encoder and an efficient decoder that effectively decodes both shallow and deep information, alleviating the indirect interactions caused by information loss and degradation between non-adjacent levels. To evaluate the model's generalization ability, we utilized a high-resolution dataset of soybean pods from field harvesting. Through experimental comparisons between manual counting and model yield estimation, we confirmed the effectiveness of the PodNet model. The experimental results indicate that PodNet achieves an R2 of 0.95 for the prediction of soybean pod quantities compared to ground truth, with only 2.48M parameters, which is an order of magnitude lower than the current SOTA model YOLO POD, and the FPS is much higher than YOLO POD. Compared to advanced computer vision methods, PodNet significantly enhances efficiency with almost no sacrifice in accuracy, providing a new solution for counting and locating dense objects.